Erythrocytes of Little Ground Squirrels Undergo Reversible Oxidative Stress During Arousal From Hibernation - Klichkhanov, Nisred K.; Nikitina, Elena R.; Shihamirova, Zainab M.; Astaeva, Maria D.; Chalabov, Shamil I.; Krivchenko, Aleksandr I. (Frontiers in Physiology, 2021)
The hibernation of small mammals is characterized by long torpor bouts alternating with short periods of arousal. During arousal, due to a significant increase in oxygen consumption, tissue perfusion, and the launch of thermogenesis in cells, a large amount of reactive oxygen species (ROS) and nitrogen (RNS) can be formed, which can trigger oxidative stress in cells. To estimate this possibility, we studied the intensity of free-radical processes in the red blood cells (RBCs) of little ground squirrels (LGS; Spermophilus pygmaeus) in the dynamics of arousal from hibernation. We found that in the torpid state, the degree of generation of ROS and RNS (8.3%, p>0.09; 20.7%, p<0.001, respectively), the degree of oxidative modification of membrane lipids and RBC proteins is at a low level (47%, p<0.001; 82.7%, p<0.001, respectively) compared to the summer control. At the same time, the activity of superoxide dismutase (SOD) and catalase (CAT) in RBC is significantly reduced (32.8%, p<0.001; 22.2%, p<0.001, respectively), but not the level of glutathione (GSH). In the torpid state, SOD is activated by exogenous GSH in concentration-dependent manner, which indicates reversible enzyme inhibition. During the arousal of ground squirrels, when the body temperature reaches 25°C, RBCs are exposed oxidative stress. This is confirmed by the maximum increase in the level of uric acid (25.4%, p<0.001) in plasma, a marker of oxidative modification of lipids [thiobarbituric acid reactive substances (TBARS); 82%, p < 0.001] and proteins (carbonyl groups; 499%, p < 0.001) in RBC membranes, as well as the decrease in the level of GSH (19.7%, p < 0.001) in erythrocytes relative to the torpid state and activity of SOD and CAT in erythrocytes to values at the Tb 20°C. After full recovery of body temperature, the level of GSH increases, the ratio of SOD/CAT is restored, which significantly reduces the degree of oxidative damage of lipids and proteins of RBC membranes. Thus, the oxidative stress detected at Tb 25°C was transient and physiologically regulated.